ANALYSIS OF COCOA SUPPLY RESPONSE IN INDONESIA - Ghufron Wahyu Priyo Cahyono; Ratya Anindita; Condro Puspo Nugroho (Socio-Economics/Agribusiness Department, 2020)
Cocoa is one of the plants used as raw material for making chocolate, where chocolate is currently popular in the world and in Indonesia. This makes cocoa consumption continue to increase. Increased cocoa consumption must be balanced with an increase in cocoa production. However, it turns out that cocoa production in Indonesia in the last five years has decreased, in addition to the condition of cocoa plantations in Indonesia that have the potential to increase. This study aims to analyze the factors that affect the supply of cocoa in Indonesia based on the number of cocoa plants produced, to analyze the factors that affect the supply of cocoa in Indonesia based on the level of cocoa crop productivity, and to estimate the elasticity of cocoa supply in the short term and long term in Indonesia. The method used in this study is co-integration test and Error Correction Model. based on the results of the analysis, it is known that the factors that influence the cocoa supply response based on the number of plants, namely the price of cocoa beans in the previous three years, interest rates in the previous three years, the number of cocoa plants produced in the previous year Influential in positive and CPO prices in three the previous year Influential in negative. Meanwhile, the factors that influence the supply of cocoa based on the level of crop productivity, namely the price of cocoa beans in the current year Influential in positive and the price of urea fertilizer in the current year Influential in negative. The short-term elasticity of cocoa supply is 0.189 and the long run is 0.347, where both are not elastic. Increased supply response can be done by government intervention to provide input subsidies to farmers and maintain maintenance on plantations so that production is high.